Pengaruh Psikologi Petani terhadap Penerapan Inovasi Teknologi Fermentasi Jagung Bose pada Gapoktan Setetes Madu Fatuleu Desa Camplong II, Kabupaten Kupang - Musa Frengkianus Banunaek; Endeyani V. Muhammad; Cokorda BDP. Mahardika; Jemseng C. Abineno; Yofris Puay; Melkianus Pobas (Jurnal Penyuluhan, 2022)
Corn is one of the important food ingredients for Indonesian people, to maximize the important role of corn as a staple food for the community, it can be done by improving the psychology about their decision to manage and consume the corn. This research aims to find out the effect of farmers’ psychological factors on the application of fermentation bose corn technology in Setetes Madu Fatuleu farmer group association. This research was held in Camplong village II Fatuleu District Kupang Regency of East Nusa Tenggara using quantitative research as an explanation survey research method and the participants of all Setetes Madu Fatuleu Farmer Group Association that cultivate the corn is amount 55 participants. Data analysis in this research using multiple linear regression analysis. The result showed: (1) psychological factors consisting of knowledge, motivation and attitudes together had a significant effect of 53,8% on the application of fermented bose corn technology in Setetes Madu Fatuleu Farmers Group Association, (2) psychological factors consisting of knowledge and each motivation has a significant effect of 46,6% for knowledge and 27,2% for the motivation factor of participant Setetes Madu Fatuleu Farmers Group Association on the application of fermented bose corn technology, while the attitude factor of the Setetes Madu Fatuleu Farmers has no effect on the application of fermentation bose corn technology.